ANALYSIS OF JOB STRESS AFFECTING THE PERFORMANCE OF SECONDARY SCHOOLS' VOCATIONAL TECHNICAL TEACHERS IN NORTH EAST, NIGERIA - Dankade, Umar; Bello, Hassan; Deba, Ahmad Aliyu (Journal of Technical Education and Training, 2016)
The study assessed the factors associated with job stress among secondary schools vocational technical teachers in the North-east sub-region of Nigeria. Literatures were reviewed based on the objectives of the study. The design of the study was a survey; a structured questionnaire consisting of 30 items was used for data collection. 160 respondents were randomly sampled from 18 vocational secondary schools (three schools from each of the six states of the zone). The data for the study were collected and analyzed using frequency and percentage. Some of the findings of the study revealed that majority of the vocational secondary school teachers are faced with serious problem of job stress largely due to work overload, large class sizes, lack of motivation and students' indiscipline leading to poor job performance, anxiety, boredom and prostration. The study further suggested that better qualified staff be employed and more classrooms be provided to promote quality teaching and finally vocational technical teachers should be effectively motivated so that they would be encourage to remain in the profession.Â